(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Raja Rao, along with Mulk Raj Anand and R. K. Narayan, is one of the three pillars of Indo-Anglian Fiction. Kanthapura (1938) is Rao’s first novel which is now considered a classic in Indian English fiction. In the present novel, Rao experiments with third person narrative through the eyes of an old woman named Achakka. Instead of using western style, he uses the ancient Puranic method of story-telling which, according to him, is true to Indian atmosphere and which gives an Indian flavor to the novel. Also, Rao tries to show the difference of language used by an educated man and an uneducated man. Further, the novelist explores the various superstitions of Indian culture. Throughout the novel, Rao uses some popular Indian words and phrases which are typical to Indian culture and by which he tries to Indianize English language.